Contratación verbal y buena fe: una visión crítica de la buena fe de los contratistas en la contratación verbal - Abel Blanco Montañés (Revista Vasca de Administración Pública)
In the courts, the notion and principle of good faith has generally worked against the Administration in cases of verbal contracting. However, it is also necessary to question or simply deny the good faith of contractors in many cases, given the impossibility of assigning them excusable ignorance of the validity of a contract that does not present any appearance of legal regularity. This article develops a critical view of the good faith of contractors or suppliers and tries to specify the consequences that the lack of good faith in their conduct may have within the legal mechanisms that the Public Sector Contracts Act establishes to purge these cases. In order to do both, the case law and the doctrine of the advisory bodies are taken into account.